Pengaruh Desinfeksi Mesin Tetas Menggunakan Ekstrak Daun Kemangi Terhadap Daya Tetas Puyuh Jepang (Cortunix Japonica) - Elgy Anggreawan; Siti Bilqis; Syaniar Sativa; Andrean Muhamad Fathir; Muhammad Rais (CV. SINAR HOWUHOWU, 2026)
The success of qual egg incubation is influenced by the sanitary condition of the incubator, as contamination by pathogenic microorganisms can increase embryonic mortality and reduce hatchability. This study aimed to analyze the effect of incubator disinfection using basil leaf (Ocimum basilicum) extract on the hatchability of Japanese quail (Cortunix japonica) eggs compared with chemical disinfection (intercide). The study was conducted in June 2026 at the Hatchery Laboratory, School of Vocational Studies, IPB University, Sukabumi, using an experimental method with two treatments, namely incubator disinfection using a chemical disinfectant (P0) and basil leaf extract (P1). A total of 88 Japanese quail eggs were used as samples, with 44 eggs assigned to each treatment. The observed parameters included hatchability and embryonic mortality. The data were analyzed using the Shapiro-Wilk test for normality, followed by the Independent Samples T-Test or the Mann-Whitney test according to data distribution. The results showed a significant difference (p<0,05), indicating that the use of basil leaf extract resulted in a higher hatchability 86,11% than the chemical disinfectant 64,29%. In addition, the basil leaf extract treatment reduced embryonic mortality by 13,63%, whereas the highest embryonic mortality was observed in the chemical disinfectant treatment 20,45%. It was concluded that basil leaf extract as a disinfectant has the potential to serve as a more effective natural disinfectant than chemical disinfectants.